Two new species of Rourea (Connaraceae) from Minas Gerais, Brazil - Toledo, Cássio A. P.; Souza, Vinicius Castro (Phytotaxa, 2019)
While developing taxonomic studies about Connaraceae in Brazil, two new species of Rourea were discovered. Rourea barbata and R. prostrata are here described and illustrated. The new taxa belong to Rourea subgen. Rourea sect. Multifoliolatae and comparisons to morphologically similar species are provided, along with notes on their distribution, habitat, taxonomy and conservation status.